Continuous Intravenous Valproate as Abortive Therapy for Pediatric Status Migrainosus. Issue 2 (March 2018) - Zafar, Muhammad S.; Stewart, Alejandra M.; Toupin, David N.; Cook, Aaron M.; Baumann, Robert J.
Abstract : Objective: This study describes the use of continuous intravenous valproate as an abortive therapy for pediatric status migrainosus. Background: Intravenous valproate as a bolus dose has been shown to be an effective abortive therapy for status migrainosus in children; however, Valproate's pharmacokinetic profile suggests that it would be safer and more therapeutic as a continuous infusion. This dosing strategy results in less serum concentration fluctuations, more consistent therapeutic effects, and less adverse effects. Methods: A retrospective chart review between August 2009 and August 2012 identified 83 patients who had presented with status migrainosus and had received continuous intravenous valproate after failing to respond to initial abortive treatment. These patients had received a 20 mg/kg loading dose, followed by continuous infusion at 1 mg/kg/h. Serum valproate levels had been drawn 4 hours and 24 hours after the loading dose. Infusion rate had been adjusted to maintain serum levels of 80 to 100 mcg/mL. Age-appropriate pain assessments had been recorded at regular intervals. Excellent response was defined as a 100% reduction in pain scores, moderate response as 50% to 99% reduction, and poor response as <50% reduction. Results: Of the 83 patients, 55 (66.2%) had reported an excellent response, 4 (4.8%) a moderate response, and 24 (28.9%) a poor response. Of those reporting an excellent response, 76% had responded within 24 hours. Nausea (8.4%) and vomiting (2.4%) had been the only reported side effects. Twenty-four hour serum levels had been within the goal range 91.9% of the time. Conclusions: Continuous intravenous valproate is safe, easy to monitor, and therapeutic in the abortive treatment of status migrainosus in pediatric patients.